Photocatalytic removal of diclofenac by Ti doped BiOI microspheres under visible light irradiation: Kinetics, mechanism, and pathways - Fuyang Liu; Jialiang Liang; Long Chen; Meiping Tong; Liu, Wen (Journal of Molecular Liquids, 2019)
BiOI microspheres doped with different amounts of Ti were fabricated and used to remove diclofenac (DCF) from water under visible light irradiation. The fabricated photocatalysts were well characterized. Ti doped BiOI microspheres were found to exhibit higher photocatalytic activity towards DCF under visible light compared with BiOI. Ti doping broadened the band gap of BiOI, which leads to a more negative conduction band edge and a higher reducing activity of photo-generated electrons, thus facilitates ·O2− production during photocatalysis. Among all the fabricated Ti doped BiOI microspheres, TB450 exhibited the highest DCF photocatalytic removal efficiency. Specifically, 99.2% of DCF (C0 = 10 mg L−1) was removed by TB450 (250 mg L−1) at pH 5 within 90 min under visible light irradiation. Scavenger experiments indicated that active species including h+, ·O2− and H2O2 played important roles in the photocatalytic process. The degradation pathway of DCF was elucidated by theoretical density functional theory (DFT) and by-products identification through liquid chromatograph mass spectrometer (LC-MS) analysis. DCF degradation pathway mainly included hydroxylation and the cleavage of CN bond. DFT calculation can well interpret the degradation mechanism and the sites of DCF molecule with high radical-attack Fukui index (f0) exhibit high reactivity. Acidic condition was found to facilitate the DCF photocatalytic removal. Due to strong photo-stability, Ti doped BiOI microspheres contained good visible-light-driven (VLD) photocatalytic removal efficiency for DCF in the fourth consecutive reused cycle. Ti doped BiOI microspheres can be employed as a cost-effective and high-efficient material to efficiently degrade emerging contaminants (e.g., pharmaceutical) from wastewaters under visible light conditions.
Keywords: Degradation pathway; DFT calculation; Diclofenac; Photocatalysis; Reuse; Ti doped BiOI microspheres